CLIENT RETENTION STRATEGIES AND CUSTOMER LOYALTY DEVELOPMENT - Marya Mujayana (Journal of Applied Management and Business, 2020)
Since satisfied clients are the most significant resources of an organization, organizations have been concentrating on creating client maintenance and dedication programs. The key reason for client maintenance endeavors is to guarantee keeping up associations with esteem including clients by diminishing their abandonment rate. Making client satisfiedness is basic for the endurance of the organization in exceptionally serious markets. In this manner, this section begins with demonstrating the noteworthiness of client maintenance promoting procedures for the organization by uncovering the financial aspects of maintenance advertising programs. Prerequisites for creating powerful client maintenance systems are clarified. At last, in the wake of talking about kinds of responsibility, this section finishes by clarifying faithfulness projects and win-back systems.